2021
DOI: 10.1039/d1cc02639a
|View full text |Cite|
|
Sign up to set email alerts
|

Optochemical control of transcription by the use of 7-deaza-adenosine-based diarylethenes

Abstract: Out of nine different 7-deaza-adenosine diarylethenes, we identified a high-performance photoswitch, suitable for the synthesis of photochromic DNA. By using solid phase synthesis, a photoresponsive T7 promotor was generated which...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 21 publications
0
19
0
2
Order By: Relevance
“…After 10 switching cycles of alternating UV and Vis irradiation under our previous standard conditions, [22,23,37] no fatigue was evident for any of the photoswitches, regardless of whether one or two methyl groups were present (Figure S6). However, these conditions were very mild (low LED power of 2.6 mW cm À 2 at 310 nm UV-light) compared to other studies.…”
Section: Reversibility and Fatigue Resistancementioning
confidence: 81%
See 1 more Smart Citation
“…After 10 switching cycles of alternating UV and Vis irradiation under our previous standard conditions, [22,23,37] no fatigue was evident for any of the photoswitches, regardless of whether one or two methyl groups were present (Figure S6). However, these conditions were very mild (low LED power of 2.6 mW cm À 2 at 310 nm UV-light) compared to other studies.…”
Section: Reversibility and Fatigue Resistancementioning
confidence: 81%
“…However, our work on photoswitchable 2'-deoxy-7-deazaadenosine derivatives had revealed that modifications to the nucleobase, namely the addition of a methyl group at the reactive α-carbon atom and the replacement of N-7, do not affect the natural ability of the nucleobase to form base pairs. [23] Moreover, we observed that two methyl groups are essential for strong photochromism of purine nucleosidebased DAEs. [24,25] These results suggested that the performance of 2'-deoxyuridine DAEs should also be improved by adding a methyl group at the α-carbon of the nucleobase in combination with a favorable substituent at the thiophene moiety (Figure 1c).…”
Section: Introductionmentioning
confidence: 90%
“…Nach 10 Schaltzyklen mit abwechselnder UV‐ und Vis‐Bestrahlung unter unseren früheren Standardbedingungen [22, 23, 37] war bei keinem der Photoschalter eine Ermüdung festzustellen, unabhängig davon, ob eine oder zwei Methylgruppen vorhanden waren (Abbildung S6). Allerdings waren diese Bedingungen im Vergleich zu anderen Studien sehr mild (geringe LED‐Leistung von 2.6 mW cm −2 bei 310 nm UV‐Licht) [38] .…”
Section: Ergebnisse Und Diskussionunclassified
“…Unsere Arbeit an photoschaltbaren 2′‐Desoxy‐7‐deaza‐adenosin‐Derivaten hatte jedoch gezeigt, dass Veränderungen an der Nukleobase, wie z. B. das Hinzufügen einer Methylgruppe am reaktiven α‐Kohlenstoffatom und der Austausch von Stickstoff N‐7, die natürliche Fähigkeit der Nukleobase zur Bildung von Basenpaaren nicht beeinträchtigt [23] . Diese Ergebnisse legen nahe, dass die Eigenschaften von 2′‐Desoxyuridin‐DAEs durch das Hinzufügen einer Methylgruppe am α‐Kohlenstoff der Nukleobase in Kombination mit einem geeigneten Substituenten an der Thiopheneinheit ebenfalls verbessert werden könnten (Abbildung 1c).…”
Section: Introductionunclassified
“…Photoswitches are compounds that can be reversibly interconverted between two isomers by light. [1][2][3] The structural difference between the two photoisomers results in distinctive physical and chemical properties such as UV-vis absorption, 4 fluorescence, [5][6][7] conductance, [8][9][10] end-to-end distance and rigidity, [11][12][13] and chemical reactivity, [14][15] leading to diverse applications in optical data storage, 16,17 photopharmacology, [18][19] super-resolution microscopy, [20][21][22][23] and sensing of species such as mercury and cysteine. 24,25 These various applications require photoswitches with optimized properties, such as high quantum yields of photoswitching, high conversion between isomers and good fatigue resistance.…”
Section: Introductionmentioning
confidence: 99%